Analisis Pendapatan Usaha Nelayan Tangkap Ikan TunaDi Kabupaten Manokwari - Nurhasana; Achmad Rochani; Ketysia Imelda Tewernusa (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
The purpose of his study aims to determine and analyze how much the income level of tuna fishing business is and what factors affect the level of tuna fishing business income in Manokwari Regency. The analytical method used is the quantitative descriptive analysis method with interview guides and questionnaires as instruments. Data analysis was performed using multiple linear regression analysis. The results showed that simultaneously and partially the variables of capital, length of time at sea, number of workers and experience at sea had a significant effect on the income of tuna fishermen in Manokwari Regency.